Analisis Persaingan Pasar Okashi Cheap di Era Digital - Riski Lainatus Sifa; Resy Tamara; Arisman Purba; Lenti Susanna Saragih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
esearch explores the impact of digital technology on market competitive dynamics, considering the role of big data, artificial intelligence (AI), digital platforms and online marketing strategies. The discussion also includes factors that influence success in competition in digital markets, such as personalization of customer experience, multichannel integration, data security, and adaptation to changing regulations and consumer trends. This analysis provides important insights for business people in facing challenges and exploiting opportunities in an increasingly dynamic and sophisticated competitive environment.